Fear of crime in the EU-15 & Hungary: assessing the vulnerability, victimization & incivilities model - Vandeviver, Christophe (2011)
This exploratory study looks into the theoretical models and measurement of fear of crime. Using multilevel modeling on data from the European Crime and Safety Survey 2005 the efficacy of vulnerability characteristics, victimization experience and incivilities perception on the prevalence, frequency and intensity measures of fear of crime is assessed while controlling for country-level characteristics. Results show that variables from all three individual-level models are significantly associated with experiencing fear of crime and additionally reveal that the basic argumentations of the victimization and incivilities model can be extended regarding the frequency and intensity of fear of crime. The arguments of the vulnerability model are only limitedly applicable to the frequency and intensity measures. Results show that victimization is a consistent predictor of fear of crime prevalence, frequency and intensity. Future research should continue examining the victimization-fear nexus